Lipids and proteins-major targets of oxidative modifications in abiotic stressed plants - Anjum, Naser A.
Stress factors provoke enhanced production of reactive oxygen species (ROS) in plants. ROS that escape antioxidant-mediated scavenging/detoxification react with biomolecules such as cellular lipids and proteins and cause irreversible damage to the structure of these molecules, initiate their oxidation, and subsequently inactivate key cellular functions. The lipid- and protein-oxidation products are considered as the significant oxidative stress biomarkers in stressed plants. Also, there exists an abundance of information on the abiotic stress-mediated elevations in the generation of ROS, and the modulation of lipid and protein oxidation in abiotic stressed plants. However, the available literature reflects a wide information gap on the mechanisms underlying lipid- and protein-oxidation processes, major techniques for the determination of lipid- and protein-oxidation products, and on critical cross-talks among these aspects. Based on recent reports, this article (a) introduces ROS and highlights their relationship with abiotic stress-caused consequences in crop plants, (b) examines critically the various physiological/biochemical aspects of oxidative damage to lipids (membrane lipids) and proteins in stressed crop plants, (c) summarizes the principles of current technologies used to evaluate the extent of lipid and protein oxidation, (d) synthesizes major outcomes of studies on lipid and protein oxidation in plants under abiotic stress, and finally, (e) considers a brief cross-talk on the ROS-accrued lipid and protein oxidation, pointing to the aspects unexplored so far.